Prolactin gene (C576A) polymorphism is associated with milk production performance in crossbred Anglo-Nubian dairy goats - MONEVA, CARLO STEPHEN O; SANGEL, PERCIVAL P; ANGELES, AMADO A; MENDIORO, MERLYN S; VEGA, RENATO S A (The Indian Journal of Animal Sciences, 2024)
Crossbred Anglo-Nubian goats (Anglo-Nubian × native goat breeds), are valued for exceptional milk production and adaptability. In-depth research on these goats is imperative to propel advancements in dairy goat breeds and enhance milk production efficiency within the region. The present study aims to assess polymorphism in prolactin (C576A) gene and determine the influence of different prolactin (PRL) genotypes to milk yield performance in crossbred Anglo-Nubian dairy goats raised from Awang, Opol, Misamis Oriental and Talay, Dumaguete City, Negros Oriental. Genomic DNA was extracted from hair follicles using commercial DNA extraction kit and PCR-RFLP was performed for the genotyping of the C576A polymorphism located in exon 5 of goats’ prolactin gene using Eco241 restriction enzyme. Genotypic frequencies of 0.56 for AA, 0.44 for AB, while allelic frequencies of 0.78 for A, and 0.22 for B were recorded. All populations followed the Hardy–Weinberg principle, except for dairy goats from Farm A located in Opol, Misamis Oriental. A two-way factorial (2 × 4) in a Randomized Complete Block Design was used to evaluate the relationship between genotypes and milk yield performance. AB genotype goats produced significantly higher milk yield traits (average daily milk yield and total milk production) than AA genotype, an indication that the polymorphism in the caprine PRL (C576A) gene influenced milk yield performance in the population of studied crossbred Anglo-Nubian goats. These results have to be validated in other dairy goat breeds.